Main street millionaire : how to make extraordinary wealth buying ordinary businesses - Sanchez, Codie
"From the founder and CEO of Contrarian Thinking, an investment empire with more than two million fans, an empowering guide to getting rich and a call to arms to save America's small businesses"--
Keywords: Success in business; Sale of small businesses